Shaping and being shaped: How organizational structure and managerial discretion co-evolve in new managerial roles - Sandhu, Sukhbir; Kulik, Carol T. (Administrative Science Quarterly)
As new roles emerge in organizations, it becomes critical to understand how organizational structure can impede or enable the managerial discretion available to role incumbents. We leverage the rich context provided by the emergent role of sustainability managers to examine the interplay between the top-down forces of structure and the bottom-up influences of managerial discretion in shaping new organizational roles over time. We analyzed qualitative data collected from in-depth interviews with sustainability managers in 21 case study organizations in India and Australia, supplemented with archival and observational data. We identified three organizational configurations, with varying levels of top-down structural and bottom-up managerial discretion dynamics at play. Each configuration had different implications for the manager$1 (Bs role. Our analysis suggests that the third configuration$1 (Bwith semi-structured formalization and a decentralized sustainability program$1 (Bprovided the most conducive conditions for managers to use their discretion to champion innovative sustainability initiatives. New managerial roles in the other configurations, however, do not have to be static. With the maturation of organizational programs and active championing by managers, the structuring of organizational functions and managerial roles can co-evolve. Our findings describe a process of (3z(Bshaping and being shaped,(3y (Bas structure and managerial discretion co-evolve over time. - Reproduced.s